PENGARUH KUALITAS PELAYANAN DAN HARGA TIKET TERHADAP MINAT BELI PENUMPANG MASKAPAI GARUDA INDONESIA DI BANDAR UDARA INTERNASIONAL SOEKARNO HATTA - Faisal Akbar El Johan (BORJUIS: JURNAL OF ECONOMY, 2024)
Technological and scientific advances have had a significant impact on many aspects of life, including transport. Air transport is growing with fierce competition between airlines especially Garuda Indonesia airlines regarding service, prices, and consumer interests given, as well as there are cases of incidents that make passengers judge poorly the quality of service provided. Some of the cases occurred were flight delays, damage to luggage, and undue food on Garuda Indonesia airlines. Garuda Indonesian airlines also failed to respond in providing solutions to problems / complaints that occurred against passengers. Then the price set by Garuda Indonesia airlines is indeed high but not comparable to the service provided. The aim of this study is to find out how much the quality of service and ticket prices influence the interest of Garuda Indonesia airline passengers in Soekarno-Hatta International Airport. The study uses quantitative research methods and was conducted from August to September 2023. In addition, the researchers used data collection techniques in the form of a questionnaire as a data collection method and a double regression analysis method. The passengers at Soekarno-Hatta International Airport are samples of this study. Based on the t test, the independent variables Quality of Service (X1) and Price (X2) have a significant influence on the dependent variables Buy Interest (Y), with a significance value of 0,000 < 0,1 and a table F value of 12,471 < 2,78. The determination coefficient (R2 ) indicates that the quality of service (x1) and price (x2) have significant influences on Buy Interests. (Y).